The impact of cultural diversity on the German housing market - Mehmet Bayar (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
This paper documents a positive impact of cultural diversity and cultural similarity on rental prices of the German districts for the years between 2004 and 2013. On the one hand, an increase of the Herfindahl index as a measure for cultural diversity of 0.1 would increase rents by over 12 percent after controlling for relevant explanatory variables and city and time fixed effects. On the other hand, an increase in the share of foreign-born individuals is associated with a decrease in rents. These results suggest an economic impact that is an order of magnitude bigger than that found in labor markets. Consequently, cultural diversity can be considered as a city-specific consumption amenity. The positive impact of cultural diversity on the local housing market mirrors the fact that inhabitants are willing to pay higher rents in cities with a high level of diversity. Natives prefer to live in culturally diverse areas, but they avoid to reside in areas where the share of foreigners is too high. These findings show that amenity considerations play a role in residential location decisions. – – Die vorliegende Studie identifiziert einen positiven Effekt der kulturellen Vielfalt und der kulturellen Nähe auf die Mietpreise der deutschen Kreise und kreisfreien Städte für die Jahre zwischen 2004 und 2013. Ein Anstieg des Herfindahl-Index, als Maß für die kulturelle Vielfalt, von 0,1 würde die Mieten um mehr als 12 Prozent erhöhen, wenn für relevante erklärende Variablen und unbeobachtete zeitinvariante Effekte kontrolliert wird. Auf der anderen Seite ist ein Anstieg des Ausländeranteils als homogene Gruppe mit einem Rückgang der Mieten verbunden. Diese Ergebnisse deuten auf eine ökonomische Auswirkung hin, die von der Größenordnung her von Effekten der Einwanderung auf den Arbeitsmärkten abweichen. Folglich kann die kulturelle Vielfalt als eine stadtspezifische Annehmlichkeit betrachtet werden. Die positive Auswirkung der kulturellen Vielfalt auf den lokalen Wohnungsmärkten spiegelt die Tatsache wider, dass die Bewohner bereit sind, höhere Mieten in Städten mit einem hohen Maß an Vielfalt zu zahlen. Die Einheimischen ziehen es vor, in kulturell diverzifizierten Gebieten zu leben, aber sie vermeiden, in Gebieten zu wohnen, in denen der Ausländeranteil zu hoch ist. Diese Ergebnisse zeigen, dass Annehmlichkeiten der Städte eine Rolle bei der Wohnortentscheidung spielen.
Keywords: F22; J61; R23; 330; Housing market; immigration; cultural background; Germany